(3EOQGQ GdTQhb Ydi CfhGQ GdHQhbs - (3CHh GdbGSe Hf YHO Gddg Hf eMeO Hf eMeO GdCfUGQjs; (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi deG WGdYJ cJGH GdGeGe TgGH GdOjf CHj GdYHGS CMeO Hf EOQjS GdbQGai GdeSei HCfhGQ GdHQhb ai EfhGA GdaQhb hSejJg HEOQGQ GdTQhb Ydi CfhGQ GdHQhb djhGab GddaX GdeYfi s
(3BNQgG (B:s
(3ai GdbSe GdKGfi YTQ UMjM hcPdc eG bGdg ai GdaQb hgh BNQ GdaQhb hGddg JYGdi CYde hgfG GfJgi GdcdGe Ydi GfhGQ GdHQhb s
(3GdejcQhajde JGdas
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
Keywords: (3CUhd Gdabgs